CLINIC-PARACLINICAL CHARACTERISTICS OF DIABETIC CHILDREN - Piantkovska, N.S. (World of Medicine and Biology, 2010)
Under our care it was 100 children, who were undergoing the medical treatment in Endocrinology Department of National Children’s Specialized Hospital “OKHMATDYT” with diagnosis of diabetes mellitus. At the age of 10-15 years old it was 74 (74 %) children, at the age of 16-18 it was 26 (26 %) children. Among examined children it was 54 (54 %) girls and 46 (46 %) boys. Clinical, electroneuromyographic and reovasogra-phic comparison allows detecting diabetic polyneuro-pathy in the disease debut. It is reasonable to implement clinical, electroneuromyographic and reovasographic comparison as screening considering diabetic polyneuro-pathy risk group among patients with Insulin-dependant diabetes.